Bibliometric Analysis: Developmental Theory of Research Studies The Growth of SMEs in the Last Five Years - Warsiyah, Warsiyah; Juhary, Ali (2023)
This study aims to analyze how research on the growth of SMEs which have been published within a period of five years starting from 2017-2022. This research method is a literature review using a bibliometric analysis approach starting from defining the keywords for micro business growth and 'Journal' in the Publish or Perish application with Google Scholar as the database. After narrowing the results by selecting a special topic. Then compiled meta data using the Vosviewer application which is used to visualize research trends. The results show that the classification of research on MSME growth is divided into 7 clusters of 70 items and 404 links with the colors Red, Dark Blue, Dark Green, Light Blue, Light Green, Orange, and Purple. Research on the growth of micro, small and medium enterprises is mostly carried out in 2017 and at least in 2022. There is still very little research on the growth of MSMEs which is shown in network visualization, Overlay Visualization and Density Visualization Vosviewer.